EFFECT OF ANTHRACYCLINE ANTITUMOR ANTIBIOTICS UPON TRANSCRIPTION ACTIVITY OF CANCER-TESTIS ANTIGENS IN MODEL EXPERIMENTS WITH HeLa CELLS - D. S. Kutilin; Kh. A. Mogushkova (Медицинская иммунология, 2019)
Cancer-testis antigens (CTA) can be used as a target for immunotherapy of various malignant tumors, including cervical cancer. However, immunotherapy is often used in combination with anthracycline chemotherapy, in particular, doxorubicin (DXR). Their effects upon expression of CTA genes have not been yet studied. Therefore, we studied the effects of doxorubicin at different concentrations and exposure time upon transcriptional profile of 17 cancer-testicular (CT) genes of HeLa CCL-2 cells. A long-term line of human cervical cancer cells (HeLa CCL-2 line) was used in this work. Culturing of HeLa CCL-2 cells was carried out in sterile culture flasks with adhesive surface and ventilated lids at 5% CO2, and 95% humidity at 37 °C, in RPMI-1640 medium with 10% fetal bovine serum, supplied with gentamicin (50 μg/ml), and different concentrations of doxorubicin: 0 μg/ml (control), 2 μg/ml, and 4 μg/ml. Expression levels of 16 RT-genes were determined by quantitative RT-PCR using a Bio-Rad CFX96 thermal cycler. Normalization of results was performed against a reference gene, and expression of tested genes in the control samples. We have found that the time of in vitroexposure, and concentration of doxorubicin exert a significant influence upon expression of MAGEA1, MAGEA3, MAGEA4, MAGEB1, MAGEB2, GAGE1, GAGE3, BAGE, CTAG1B, XAGE3, NY-ESO1, PRAME1 and SYCP1 genes, however, without affecting the SSX2, MAGEA2, GAGE4 and MAGEC1 expression, and DXR concentration as a single factor did not affect MAGEB1 and MAGEB2 expression. Time of response to DXR effects enabled us to discern early cancer testicular genes with increased expression (MAGEA1, MAGEA3, MAGEA4, NY-ESO1, SYCP1), reduced expression (GAGE1 and BAGE), and late inducible testicular genes (GAGE3 and XAGE3). These results must be taken into account when carrying out immunotherapy based on the dendritic-cell vaccine technology.